Association between myocardial layer-specific strain and high 10-year risk of atherosclerotic cardiovascular disease in hypertension—findings from the China-PAR project study - Chen, Jianxiong; Yang, Xiaohuan; Li, Xinyi; Jin, Lin; Wu, Lingheng; Zhang, Mengjiao; Du, Lianfang; Luo, Xianghong; Li, Zhaojun (Frontiers in Cardiovascular Medicine, 2024)
Objectives Myocardial layer-specific strain is a sensitive tool for detecting myocardial dysfunction. The objective of this study was to assess changes in the left ventricle (LV) function using myocardial layer-specific strain and its association with 10-year atherosclerotic cardiovascular disease risk (10Y-ASCVDR) in individuals with hypertension (HP). Methods The parameters of LV structure, including layer-specific global longitudinal strain (GLSww, GLSendo, GLSmid, GLSepi) and layer-specific global circumferential strain (GCSww, GCSendo, GCSmid, GCSepi), were analyzed by two-dimensional speckle-tracking echocardiography in 239 hypertensive patients and 124 control subjects. In addition, participants were divided into low-risk (LR) and high-risk (HR) subgroups according to 10Y-ASCVDR scores . The correlation between myocardial layer-specific strain and 10Y-ASCVDR was further analyzed by the restricted cubic spline (RCS) function. Results The values of GLSww, GLSepi, GLSmid, and GLSendo were significantly lower in HP patients with HR than in HP patients with LR and controls (p < 0.05). However, no significant differences in layer-specific GCS were observed between the groups (p > 0.05). RCS analysis revealed that 10Y-ASCVDR exhibited a significant J-shaped relationship with layer-specific GLS and GCS. After adjusting for confounding factors, GLSww (β = 0.156, p = 0.042), GLSmid (β = 0.161, p = 0.032), GCSendo (β = 0.163, p = 0.024), and GCSmid (β = −0.175, p = 0.030) were identified as independent influencing factors for high 10Y-ASCVDR. Conclusions In hypertensive patients, myocardial layer-specific strain, especially GLS, sensitively detected LV dysfunction and showed a significant J-shaped relationship with 10Y-ASCVDR. GCSmid may have a compensatory effect on myocardial impairment. LV myocardial layer-specific strain may help to understand the early compensatory mechanisms of the myocardium in hypertension.